Spectrophotometric Determination of Metformin via Schiff Base Formation with 2-Hydroxy-1-Naphthaldehyde - Noman, Reem Salwan (American Journal of Biomedicine and Pharmacy, 2026)
A sensitive and straightforward spectrophotometric technique for measuring metformin levels was established in this work. The process is reacting 2-hydroxy-1-naphthaldehyde in an acidic solution to create a Schiff base, which has a high absorbance at 453 nm and an orange-yellow hue that indicates Schiff base production. The calibration curve validated the quantitative approach by demonstrating a linear relationship for values between 2 and 23 µg/mL, as indicated by the correlation coefficient R² = 0.9995. The method's great sensitivity and accuracy were demonstrated by the molar absorbance of 3693.976 L/mol/cm² and the Sandel index sensitivity of 0.0767 µg/cm² with a recovery rate of 100.53%. With a standard deviation of 0.0479%, the accuracy and repeatability were good. Additionally, the quantification limit was 0.098 µg/mL and the detection limit was 0.032 µg/mL. This approach is thought to be extremely sensitive to the medication. Because the ratio between the reactant and the medication was 1:1, the correctness of the standard technique was checked using the Job approach and the suggested chemically equivalent molar ratio. The concentration of metformin in the pharmaceutical formulation was satisfactorily established using this approach.